Analisa Strategi Pemasaran Dalam Rangka Meningkatkan Volume Penjualan pada Usaha Kerupuk Sawargi Muara Bulian - Endang Meiliani; Sopian Sopian (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2022)
In this research in general is to analyze the marketing strategy applied to the Home Industry of Sawargi Crackers in Pal 4. Muara Bulian-Jambi District, in order to increase sales volume. The purpose of this research is to find out specifically whether the marketing strategy has been effective or not in order to increase sales volume. The method of analysis in this research is a qualitative descriptive method, which is to compare the reality that exists in the Home Industry of the Sawargi Cracker Industry in pal 4. Muara Bulian-Jambi District with concepts or theories related to the problem being studied. So far, the Home Industry of Sawargi Crackers Industry in pal 4. Muara Bulian District in its activities has used a marketing strategy which includes product strategy, price strategy, promotion strategy and distribution strategy, distribution which is quite good but there are still obstacles and shortcomings within the company's internal and external company. So the research results show that the marketing strategy is not optimal in increasing sales volume.